Compilation of early warning indicators for foreign trade employing a cut-off survey - Jorma Hilpinen (Bank of Finland, 1995)
In order to bridge the lack of the official foreign stade statistics compiled by the Board of Customs caused by Finland's entry into the EU and to secure the availibility of current account estimates with a five week delay, the Bank of Finland decided in the autumn 1994 that a special survey for foreign trade will be built.It was felt necessary that the balance of payments statistics must continue to come out without any halt.It seems evident that within rather wide limits exports and imports can be estimated with the cut-off survey.However, monthly variations being very large, it is of utmost difficulty to give precise monthly estimates for the trade balance.The current preliminaries produced by the Bank as well as by the Customs may give wrong signals to the market if single monthly observations are concerned. The Bank of Finland survey data may describe the underlying developments in the foreign stability with reasonable reliability. In addition, the use of robust economic relationships could be one way to economize and to speed up statistical systems.However, to have consistent short term information on trade balance, only one reliable information system is no doubt preferred.Therefore, the Board of Customs should make every effort to make their statistical system functional so that information are available with only a few weeks delay and the reliability of the old foreign trade statistic could be reached.
URN:NBN:fi:bof-20140807188
Keywords: 330